Isolation and Identification of Bacteria from Raw Materials Contaminated by Rope-producing Bacteria - ANASTASIA ASRI WIDYASARI; STELLA MAGDALENA; BIBIANA WIDIYATI LAY (Indonesian Society for microbiology, 2015)
Ropey bread is a bacterial spoilage condition of bread. The spoilage involved in ropey bread is primarily due to Bacillus subtilis. Several studies have shown that rope spoilage can be controlled using antimicrobial agents such as acetic acid, lactic acid, and quaternary ammonium cations (QACs/quats). This research consisted of five main steps: isolation, identification, confirmation, and molecular characterization of bacteria from raw materials contaminated by rope-producing bacteria, and antimicrobial test against rope-producing bacteria. The confirmation test was done in order to determine the rope-producing ability of isolates suspected as Bacillus sp. There were two different treatments in this test. In the first treatment, the inoculums were mixed with bread dough. In the second treatment, each slice of loaf was placed into a petri dish, uniformly soaked with inoculums. The first treatment did not show rope spoilage for all of the loaves, however, 6 of 11 loaves in the second treatment developed rope. The largest inhibition halos for antimicrobial test were produced by quats. This means quats is the strongest antimicrobial agent against rope-producing bacteria. The molecular characterization showed that all of the suspected isolates had 98–99% similarity to Bacillus subtilis.